Robustness assessment of a deterministically designed sacrificial cladding for structural protection. (1st August 2021) - Rebelo, H.B.; Cismasiu, C.
Highlights: Scatter of key parameters must be considered in the design of sacrificial claddings. Inadequate sacrificial claddings might hinder the element blast performance. Deterministic design may yield solutions against safety. Probabilistic design yields lower admissible charge weight. Abstract: Being able to efficiently mitigate the effects of blast loads on structures, sacrificial cladding solutions are increasingly used to protect structural elements from the effects of accidental explosions and/or terrorist attacks. The present study analyses the loss of effectiveness of a deterministically designed sacrificial cladding when variability in the material properties and uncertainties in the mechanical model are considered. The results of an experimental campaign are used to validate the numerical models that allow the deterministic design of a sacrificial cladding which successfully improves the blast resistant capabilities of a given structural element. Nonetheless, it is shown that, taking into account the probabilistic variability of key parameters is of vital importance when designing sacrificial cladding solutions, since, when not properly designed for the structural element it intends to protect, adding a sacrificial cladding might negatively impact its blast resistant capabilities. Additionally, it is concluded that the deterministic approach might be against safety. In the reported case study, when comparing the admissible charge weight yielding from the deterministic and probabilistic approaches, one verifies that the former allows a higher charge weight.